Digital Technology Adoption and Participation in GVC: An Empirical Study on Indonesia Micro and Small Manufacturing Firms - Eisha Maghfiruha Rachbini; Bahrul Maarif (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
MSMEs have become the backbone of Indonesia economy and promote inclusive economic development. However, Indonesia MSMEs’ participation in global value chain (GVC) is still limited. The development of digital economy in Indonesia might benefit MSMEs to access resources and inputs, expand to larger market, not only domestic market, but also international market. Digital transformation in economy supports their performance, i.e., increase in market share, business innovation, and more efficient business operation. Digital economy might offer opportunities for MSMEs to become parts of GVC. Since Indonesia experienced rapid development in digital economy, in which more MSMEs utilize digital technologies, such as internet and digital platform, this study aims to observe whether MSMEs digital and technology adoption will increase their probability to participate in global value chain. Therefore, this study aims to observe whether MSMEs digital and technology adoption will increase their probability to participate in GVC. This study uses non-linear probability model (NPM) is to analyze firm-level microdata from Indonesia micro and small manufacturing firms, a survey dataset from Indonesia Statistics (BPS). There are still limited studies particularly for Indonesia MSMEs participation in GVC and their digital adoption in Indonesia. By observing large dataset from firm-level data, the result of this paper provides comprehensive analysis and empirical evidence on how technology adoption for MSMEs relates to probability of MSMEs participation in GVC.